Caso de estudio: exportación de polvo compacto en base de aceite de sacha inchi a Colombia - Espinoza Badillo, Kimberly Kelly (2019)
The present project consists in studying the feasibility of exporting a premium cosmetic product for women made from natural ingredients to Colombia, being its main ingredient an exotic product of the Peruvian Amazon. To achieve the aforementioned, information has been collected from various virtual sources both at primary and secondary level. The primary sources are information collected by Colombian government institutions, as well as universities that conducted studies through sampling and interviews with the population. Secondary sources are information collected from magazines, research institutions and various online texts. The project in question is made up of seven chapters, which have been distributed as follows: Chapter I: The market opportunity, the business idea is described and the product to be developed is detailed. Chapter II: Identify the target demand and the main characteristics of the existing offer. Chapter III: An analysis of the macro environment of the country to be exported is carried out in a matrix that allows identifying the main external factors. Chapter IV: Goals and strategies of the operations plan are planted, and the process flows for the production of the good to be exported are identified. Chapter V: Goals and strategies of the supply plan are planned and the flows of the logistic processes and operators of entry and exit for the export of the product are identified.